1999
DOI: 10.1021/bi991728z
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct ER/IC γ-Secretase Competes with the Proteasome for Cleavage of APP

Abstract: The deposition of amyloid-beta peptides (Abeta) in senile plaques (SPs) is a central pathological feature of Alzheimer's disease (AD). Since SPs are composed predominantly of Abeta1-42, which is more amyloidogenic in vitro, the enzymes involved in generating Abeta1-42 may be particularly important to the pathogenesis of AD. In contrast to Abeta1-40, which is generated in the trans-Golgi network and other cytoplasmic organelles, intracellular Abeta1-42 is produced in the endoplasmic reticulum/intermediate compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
64
1
1

Year Published

2001
2001
2005
2005

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 36 publications
7
64
1
1
Order By: Relevance
“…In previous studies, peptide aldehydes such as MG132 were thought to inhibit A␤ and p3 peptide secretion by blocking ␥-secretase cleavage of the COOH-terminal fragment of APP (12,13,17,18). This conclusion was based on the observation that CTFs were detectable in cells incubated with peptide aldehydes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous studies, peptide aldehydes such as MG132 were thought to inhibit A␤ and p3 peptide secretion by blocking ␥-secretase cleavage of the COOH-terminal fragment of APP (12,13,17,18). This conclusion was based on the observation that CTFs were detectable in cells incubated with peptide aldehydes.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators reported that lactacystin increased secretion of both A␤40 and A␤42 from SH-SY5Y cells (14). The proposed explanation for these increases is that inhibition of the proteasome prevents degradation of both full-length and COOH-terminal fragments of APP making more of each available for cleavage by the ␣-and ␥-secretases, respectively (18). We reasoned that, if lactacystin disrupted ER-associated degradation of APPSw in a manner similar to other transmembrane proteins (25)(26)(27)(28), then more full-length protein would also be available for cleavage by ␤-secretase.…”
Section: Characterization Of Elisas For Detection Of Full-length App mentioning
confidence: 99%
See 3 more Smart Citations